2001
DOI: 10.1093/emboj/20.12.3262
|View full text |Cite
|
Sign up to set email alerts
|

A broad host range replicon with different requirements for replication initiation in three bacterial species

Abstract: Plasmid RK2 is unusual in its ability to replicate stably in a wide range of Gram-negative bacteria. The replication origin (oriV) and a plasmid-encoded initiation protein (TrfA; expressed as 33 and 44 kDa forms) are essential for RK2 replication. To examine initiation events in bacteria unrelated to Escherichia coli, the genes encoding the replicative helicase, DnaB, of Pseudomonas putida and Pseudomonas aeruginosa were isolated and used to construct protein expression vectors. The purified proteins were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
77
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 53 publications
2
77
1
Order By: Relevance
“…The protocol and bacterial strain used for the purification of the E. coli β-clamp were kindly provided by D. Bastia (Medical University of South Carolina, Charleston, SC). E. coli proteins DnaA-His6, DnaB-His6, DnaC, and ClpX were purified as described (43,(47)(48)(49). All TrfA preparations used in the tests were N-terminally histidine-tagged 33-kDa versions of TrfA.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol and bacterial strain used for the purification of the E. coli β-clamp were kindly provided by D. Bastia (Medical University of South Carolina, Charleston, SC). E. coli proteins DnaA-His6, DnaB-His6, DnaC, and ClpX were purified as described (43,(47)(48)(49). All TrfA preparations used in the tests were N-terminally histidine-tagged 33-kDa versions of TrfA.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of trfA Mutations-Plasmid pGC1 (20) was used to express His6TrfA-44(M98L/G254D/S267L), a variant of TrfA-44 that has six histidine residues inserted between the first amino acid (Met) and the second amino acid (Asn) of the native protein to allow for ease of purification, the M98L amino acid substitution that replaces the native methionine start of TrfA-33 with a leucine and thus eliminates TrfA-33 expression, and the G254D and S267L changes that result in a primarily monomeric form of the protein. A previous study had shown that although wild type TrfA protein is primarily a dimer in solution, it was the monomeric form that was essential for replication initiation activity (26).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids expressing the TrfA-44 N-terminal mutants were transferred into E. coli strain JP313 to overexpress and purify the proteins as described previously for TrfA-44 (20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations